APPROACHES TO THE STUDY OF POVERTY IN THE WESTERN REGION: THE CANTONS OF NARANJO, PALMARES AND SAN RAMÓN - Arroyo Navarro, Illiana (2014)
The object of the investigation proposed in this paper is aimed at identifying the changes that have resulted in family structures from the implementation of strategies, the current crisis, specifically in the cantons of Naranjo, Palmares y San Ramon. The impact of the study is designed to contribute to the knowledge of the family situation of the Western Region of Costa Rica in the context of the crisis of capital.